Tribological Properties of EN-GJL-150 grey Cast Iron Composites Produced Using Porous SiC and Al₂O₃ Inserts - Piątkowski, J.; Wojciechowski, M.; Gródek, K. (Archives of Foundry Engineering, 2026)
The article presents the tribological properties of a newly developed cast iron–ceramic composite designed for modern braking systems, such as brake discs. The composite matrix consists of grey cast iron with flake graphite (EN-GJL-150), while the reinforcing phase comprises 10% SiC and 10% Al₂O₃ particles applied onto a porous structure. Tribological tests were performed using a pin-on-disc setup, and the results were compared with a standard friction material P50 094, representing PEX-type brake pads. The results indicate that reinforcing the matrix with ceramic particles significantly alters the tribological wear mechanism. Composites EN-GJL-150+SiC and EN-GJL-150+Al₂O₃ showed an almost fivefold reduction in mass loss compared to pure cast iron. In the tested pairings, wear of the friction material was also reduced, suggesting a synergistic improvement in the durability of the entire tribological system. The coefficient of friction for cast iron samples reinforced with SiC and Al2O3 ranged from μ = 0.20–0.30, in contrast to the large variations (μ = 0.16–0.46) observed in cast iron without reinforcing particles. In composites containing porous ceramic inserts, no characteristic running-in period to reach stable friction values was observed. The obtained results of reduced wear of friction components and lower scatter of the coefficient of friction for grey cast iron-based composites are promising. However, further studies are required, mainly for a comprehensive evaluation of other functional properties, including the selection of friction pad material and reduction of environmental dust from wear products, as required by the new European Union directives (e.g., EURO 7 standards).